Serum Vitamin D Level and Risk of Community-Acquired Pneumonia: A Case-Control Study - Liyanage, Guwani; Kaneshapillai, Anusha; Kanthasamy, Suthesan (Interdisciplinary Perspectives on Infectious Diseases, 2021)
Introduction. Recent research has shown conflicting evidence on the connection between vitamin D deficiency and community-acquired pneumonia (CAP) in children. Thus, we hypothesized that vitamin D deficiency could be a risk factor for CAP. Methods. Hospitalized children between 2 and 60 months with physician-diagnosed, radiologically confirmed severe community-acquired pneumonia (CAP) were enrolled as cases. Age-matched controls were enrolled from immunization and weighing clinics. A blood sample was collected to assess serum 25-(OH)D concentration. Unconditional logistic regression was done to examine the independent association of vitamin D level with community-acquired pneumonia. Results. Seventy-four children (females: 68%) were included. Overall, 27% had vitamin D deficiency (<20 ng/mL) and 37.8% had insufficiency (20–29 ng/mL). The vitamin D level ranged from 8.67 to 46.2 ng/mL. There was no statistically significant difference in 25(OH)D levels in controls and cases (p=0.694). In unconditional logistic regression, 25(OH)D concentration was not a determinant of CAP (OR: 0.99, CI: 0.937–1.044, p=0.689). This lack of association remained after adjustment for age, gender, income, crowding, and exposure to passive smoke (OR: 0.99, CI: 0.937–1.065, p=0.973). Household income was significantly associated with CAP (OR: 0.11, 95% CI: 0.021–0.567, p=0.008). Conclusion. Two-thirds of the children with CAP had vitamin D deficiency/insufficiency. In comparison with healthy controls, vitamin D level was not a significant determinant of community-acquired pneumonia. It informs that further multisite research is required using more rigorous scientific methods for conclusive evidence on the relationship between vitamin D and CAP.